Systemic therapies for metastatic renal cell carcinoma in the second-line setting: A systematic review and network meta-analysis. Issue 37 (16th September 2022) - Liao, Yang; Hou, Haifeng; Han, Zhenhua; Liu, Ying
Abstract : Objectives: To perform a systematic review and network meta-analysis to compare the survival benefit and safety profile of current available second-line treatment options of metastatic renal cell carcinomav. Methods: PubMed, EMBASE, Web of Science, and Cochrane Library were systematically researched for eligible articles which were published before July 20, 2021. Studies comparing overall/progression free survival (OS/PFS), objective response rate (ORR), and/or adverse events (AEs) in patients with metastatic renal cell carcinomav were included. Results: Nine trials (with 4911 patients) were finally included for final network meta-analysis. Cabozantinib, lenvatinib, and lenvatinib plus everolimus were associated with significantly better PFS, OS, and ORR compared with everolimus, and lenvatinib plus everolimus emerged as the best option. As for grade 3 to 4 AEs, nivolumab showed significantly lower risk of AEs compared with everolimus. Other included treatments were associated with significantly increased risk of AEs. When comprehensively assessed the efficacy and safety of included treatments based on the ranking analysis of PFS, ORR, and grade 3 to 4 AEs, lenvatinib plus everolimus, cabozantinib, and nivolumab showed superior efficacy over other treatments, with relatively lower risk of grade 3 to 4 AEs. Conclusions: Among all included therapies, Lenvatinib plus everolimus was identified as the most effective treatment approach, with the best PFS, OS, and ORR. nivolumab was associated with decreased incidence of grade 3 to 4 AEs among included treatment therapies. When comprehensively evaluated the efficacy and safety of included treatment options, lenvatinib plus everolimus, cabozantinb, and nivolumab were associated with better survival benefits and lower risk of AEs. Future studies should focus on the direct comparison of different second-line treatment in real-world populations.